Pulmonary function testing & interpretation - Welte, Tobias (BioMed Central, 2012)
James E Hansen. Pulmonary Function Testing & Interpretation. 1st edition. New Delhi: Jaypee Brothers Medical Publishers, 2011, 261 pp., ISBN 978-93-5025-105-8